Behavior Intention to Use dan Use Behavior Mahasiswa dalam Menggunakan E-Learning dimasa Covid-19 - Muhammad Ikhlash; Herjunda Faghfirka Tama (JURNAL AKUNTANSI, EKONOMI dan MANAJEMEN BISNIS, 2021)
Responding to Covid-19 which was used as a global pandemic, Batam State Polytechnic decided the online learning process, causing an increase in the intensity of e-learning users. This study aims to determine the intentions and behavior of students in the use of e-learning. This research is limited in scope to examine the effect of performance expectancy, effort expectancy, social influence, work-life quality, hedonic motivation on behavior intention to use, and behavior intention to use on student use behavior in using e-learning. The type of research used is quantitative, with a research sample of 94 respondents. Data was collected by distributing questionnaires, then analyzed using Smart PLS version 3.0 to test instruments and hypotheses. The results showed that performance expectancy and hedonic motivation had a positive effect on behavior intention to use, while effort expectancy, social influence, work-life quality had no effect. The behavioral intention to use variables has a positive effect on use behavior.